Impact of two bioinsecticide botanical products (azadirachtin and rotenone) on the arthropofauna captured by pitfall traps on tomatoes in Ica, Peru - LANNACONE-OLIVER, JOSÉ ALBERTO; MONTORO-ZAMORA, IMELDA (Revista Colombiana de Entomología, 2002)
The impact of two botanical bioinsecticides (azadirachtin [Azadirachta indica "Neem tree"] and rotenone [Lonchocarpus utilis "Barbasco"] was evaluated on the soil macrofauna and mesofauna. The study involved natural enemies on tomato crop in lea valley, against conventional chemical pesticides used alternatively by the farmer, during the different phenological phases of tomate culture. The present work was carried out between June and September 1997. The experimental area was 1.200 m2. The experimental design used was a CRDB, with three replicates. The five treatments were: azadirachtin (two doses), rotenone (two doses) and chemical pesticides, used in rotation by the farmer. Six pitfall traps were evaluated by each dose and recollected every 15 days on average. We caught 3742 specimens during all the phenological phases of tomato crop, belonging to 10 taxa, 9 were from clase Insecta and only one was for Arachnida. Twenty-nine families were identified among them. Coleoptera showed the highest number of families with eight, then Hemiptera, Hymenoptera, and Lepidoptera with four families. The lowest number was shown by Collembola, Dermaptera, and Thysanoptera with one family each. Seventy-one percent were aereal and 29% terrestrial. The highest ratio were predators (45%), phytophagous (29%), decomposers (16%) and finally parasitoids (10%). The doses of azadirachtin showed the highest index of the diversity of Shannon and of biological control at the family level in comparison with the farmer chemical management. We did not observe differences between azadirachtin and rotenone when the abundance of the arthropod fauna at family and order level. trophic guild and average length were analyzed. We found differences between azadirachtin and chemical pesticides when all families were analyzed in total, excluding three of them (Tenebrionidae, Cixiidae, and Gelechiidae), and among the abundance evaluated at the order level, excluding Coleoptera. The number of watering and the time of exposure of the soil traps did not significantly influence the diversity of the arthropod fauna found on azadirachtin, rotenone, and conventional chemical. The index of biodiversity of Shannon was the parameter that permitted detection of significant differences among treatments.